Increased adherence to treatment guidelines for lower urinary tract infections in out–of–hours primary care settings following a simple intervention strategy: Vpliv enostavne intervencije na večje upoštevanje smernic pri zdravljenju bolnic z nezapleteno okužbo spodnjih sečil v dežurnih ambulantah na primarni ravni - Klemenc–Ketiš, Zalika; Kersnik, Janko (Acta Medico-Biotechnica, 2021)
Aim: The aim of this study was to determine whether a simple intervention could foster adherence to treatment guidelines in women with uncomplicated lower urinary tract infections (LUTIs) in after–hours primary care settings.Methods: This was a cluster, randomised, prospective intervention study in female patients conducted in 20 out–of–hours primary care (OOHC) settings in Slovenia (10 in the intervention group and 10 in the control group). In each OOHC centre, we included 10 consecutive patients with LUTIs who sought evaluation by a physician, called in for advice, or called in for a home visit. The OOHC centres in the intervention group received a poster with a schematic presentation of LUTI treatment  treatment guidelines, which was displayed on the wall in the OHC practice.Results: Of 20 OOHC centres, 14 were willing to participate in the study (seven in the intervention group and seven in the control group). The final sample consisted of 118 (59.0%) female patients (64 in the intervention group and 54 in the control group). The mean age of the sample was 43.2 ± 17.3 years (40.2 ± 16.4 years in the intervention group and 46.7 ± 17.8 years in the control group). Adherence to guidelines was confirmed in 42 patients (32 in the intervention group and 10 in the control group; p = 0.004).Conclusions: A simple intervention can significantly enhance the adherence to treatment guidelines in patients with LUTIs managed in an OOHC centre.
Keywords: urinary tract infection; primary care; intervention studies